Spectral Caustics in Attosecond Science - Dudovich N.; Bruner B. D.; Pedatzur O.; Raz O. (EPJ Web of Conferences, 2013)
A unique type of singularity common in wave phenomena, known as caustics, links processes observed in many different branches of physics [1]. We investigate the role of caustics in attosecond science and in particular the physical process behind high harmonic generation. By exploiting singularities of the three-step model that describes HHG, we can manipulate and enhance specific features in the emitted harmonic spectrum. This new level of control holds promises in both scientific and technological aspects of attosecond science, and provides a deeper insight into the basic mechanism underlying the high harmonic generation process.